Evaluation of renal functions in children with congenital heart disease before and after cardiac angiography - Noyan, Aytül; Küçükosmanoğlu, Osman; Yıldızbaş, Dinçer; Özbarlas, Nazan; Anarat, Ali; Anarat, Rüksan (The Turkish Journal of Pediatrics, 1998)
Radiocontrast nephrotoxicity, which has increased in incidence with widespread use of radiological methods in medicine, is a serious complication of radiocontrast materials. In this study, we have prospectively investigated whether children with cyanotic congenital heart disease are at risk for radiocontrast nephrotoxicity with the use of a nonionic low osmolar contrast agent. Thirty-five children (17 cyanotic and 18 acyanotic patients) who underwent diagnostic cardiac catheterization were subjects of the study. The age range was from five days to 13 years. The volume of contrast material was 3.11 ± 1.37 ml/kg in cyanotic patients and 2.67 ± 0.86 ml/kg in acyanotic patients. Blood samples and timed urine samples were taken from all patients 24 hours before and 48 hours after cardiac catheterization. Blood urea nitrogen, creatinine, sodium, and phosphorus in serum, and creatinine and N-acetyl-β-D-glucosamine in urine were analyzed. There was not a statistically significant difference between the values before and after angiography. As a result, we could find no evidence of radiocontrast nephrotoxicity with the use of a nonionic contrast agent in cyanotic and acyanotic patients who underwent cardiac angiography.